2020
DOI: 10.5430/ijfr.v11n4p546
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Performance Matter? Evidence on the Impact of Liquidity and Firm Size on Stock Return in Indonesia

Abstract: In the modern era, stock investment can attract domestic investors or foreign investors. The objective is to invest their funds at the capital market that expect higher stock returns. The study aims to analyze factors that can affect stock returns and know the mediating effect of return on equity. The object of this research is the property and real estate sector that is listed on the Indonesia Stock Exchange from 2013 to 2018. This research used debt to equity ratio, current ratio, total asset turnover, firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Over-reliance on debt financing may increase the business' riskiness that leads to financial problems which eventually deteriorate the companies' activities and performance. However, it found that the relationship between leverage and company performance to be positive in other studies such as Chabachib et al, (2020). It argued that higher debt financing would restrain managerial discretion, encourage management to strategise their activities to obtain higher profits, gain creditors confidence, and boost the growth of business activities (Chabachib et al, 2020;Hedija & Němec, 2021).…”
Section: Leverage and Company Performancementioning
confidence: 94%
See 1 more Smart Citation
“…Over-reliance on debt financing may increase the business' riskiness that leads to financial problems which eventually deteriorate the companies' activities and performance. However, it found that the relationship between leverage and company performance to be positive in other studies such as Chabachib et al, (2020). It argued that higher debt financing would restrain managerial discretion, encourage management to strategise their activities to obtain higher profits, gain creditors confidence, and boost the growth of business activities (Chabachib et al, 2020;Hedija & Němec, 2021).…”
Section: Leverage and Company Performancementioning
confidence: 94%
“…However, it found that the relationship between leverage and company performance to be positive in other studies such as Chabachib et al, (2020). It argued that higher debt financing would restrain managerial discretion, encourage management to strategise their activities to obtain higher profits, gain creditors confidence, and boost the growth of business activities (Chabachib et al, 2020;Hedija & Němec, 2021). Therefore, the relationship between leverage and company performance is indecisive and worth to be investigated.…”
Section: Leverage and Company Performancementioning
confidence: 96%
“…Matthew et al [5] suggested that long-term debt and return on assets (ROA) have favorable correlation. Chabachib et al [6] found a positive relationship between leverage and company performance. Since higher debt financing can further incentivize management to capture profits and contribute to positive corporate performance.…”
Section: Leverage and Company Performancementioning
confidence: 98%
“…Padahal, perusahaan juga harus berorientasi pada value. Demi mengatasi masalah ini, solusinya adalah dengan penggunaan metode Economic Value Added [10,18,19,31,32].…”
Section: Hubungan Ukuran Perusahaan Sebagai Variabel Moderasi Dalam H...unclassified